Carbon negative methanol production for CO2 utilization: Process design and 4E analysis - Tang, Zongyue; Zhang, Leiyu; Wang, Lei; Gao, Ruxing; Jun, Ki Won; Kim, Seok Ki; Zhang, Chundong; Yang, Yingju; Wan, Hui; Guan, Guofeng (Energy, 2024)
To produce alternative fuel and reduce CO2 emissions, the CO2-to-methanol (CTM) process is currently considered to be an effective technical pathway. However, the base CTM process suffers from high energy consumption and low carbon efficiency. Therefore, this work proposed an optimized CTM process integrating double-effect distillation, waste heat recovery, and H2 stripping technologies. Compared to the base CTM process, the optimized CTM process significantly enhances the techno-economic-environmental performances. Meanwhile, it realizes zero external heat requirements and negative carbon emissions. In order to quantitatively evaluate the improvements in the process performances, we conducted detailed technical-economic-environmental analyses. From the technical perspective, the energy efficiency and exergy efficiency of the optimized CTM process are 10.28 % and 4.84 % higher than that of the base CTM process, respectively. From the economic perspective, the methanol production cost in the optimized CTM process is lower by 18.40 $/tonne MeOH compared to the base CTM process. As for the environmental perspective, the GWP of the optimized CTM process is reduced by 336.42 kg CO2-eq/tonne MeOH compared with the base CTM process. In summary, the optimized CTM process offers an energy-efficient, cost-saving, and environment-friendly solution for CO2 conversion.
Keywords: CO 2 emission; CO2 hydrogenation; Environmental analysis; Methanol production; Methanol synthesis; Processes integrations; Techno-economic-environmental analyze; Techno-economics; Thermal; Thermal self-sufficiency; CO2 hydrogenation; Methanol synthesis; Process integration; Techno-economic-environmental analysis; Thermal self-sufficiency